Gestational diabetes in Malaysia : a systematic review of prevalence, risk factors and outcomes - Cheong, Lieng Teng; Foo, Ken Yong; Ka, Mun Lum; Shen, Yung Toh; Chan, Xuan Hii; Sivalingam Nalliah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Gestational diabetes mellitus (GDM) is glucose intolerance first diagnosed during pregnancy. In Malaysia, the prevalence, risk factors, and maternal/foetal outcomes vary somewhat among the local studies. In this systematic review of Malaysian studies, we synthesise relevant data from 13 journal articles (including 10,285 women with gestational diabetes). A meta-analysis of twelve datasets showed a prevalence of 21.5% (95% CI 17.3 to 25.9%, random effect model). Clinical factors in the mother found to increase her risk of GDM were consistent with international data. A meta-analysis of complications showed statistically significant increase for macrosomia (OR 3.08, 95% CI 1.77 to 5.36) but not for pre-eclampsia (OR 1.44, 95% CI 0.52 to 4.00) and caesarean delivery (OR 1.31, 95% CI 0.98 to 1.75). The high prevalence of gestational diabetes mellitus and documented adverse consequences support the need for universal screening of this condition in all pregnant women in Malaysia.